Leadership and Organizational Outcomes Meta-Analysis of Empirical Studies - Karadağ, Engin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book focuses on the effect of leadership on organizational outcomes and summarizes the current research findings in the field. It addresses the need for inclusive and interpretive studies in the field in order to interpret leadership literature and suggest new pathways for further studies. Appropriately, a meta-analysis approach is used by the contributors to show the big picture to the researchers by analyzing and combining the findings from different independent studies. In particular, the editors compile various studies examining the relationship between the leadership and thirteen organizational outcomes separately. The philosophy behind this book is to direct future research and practices rather than addressing the limits of current studies.
Conceptual Perspectives on Leadership -- Introduction to Meta-Analysis -- The Effect of Leadership on Job Satisfaction -- The Effect of Leadership on Organizational Commitment -- The Effect of Leadership on Organizational Trust -- The Effect of Leadership on Organizational Citizenship -- The Effect of Leadership on Organizational Culture -- The Effect of Leadership on Organizational Climate -- The Effect of Leadership on Organizational Performance -- The Effect of Leadership on Organizational Stress -- The Effect of Leadership on Organizational Burnout -- The Effect of Leadership on Organizational Health -- The Effect of Leadership on Organizational Learning -- The Effect on Leadership on Conflict Management -- The Effect of Leadership on Organizational Justice -- Discussion, Limitations and Suggestions.
Keywords: Leadership; Organization; Planning; Economic sociology; Industrial psychology; Business Strategy/Leadership.; Organization; Organizational Studies, Economic Sociology; Industrial and Organizational Psychology